PENEGAKAN HUKUM LINGKUNGAN DI BIDANG PERTAMBANGAN - Franky Butar Butar (Yuridika, 2010)
The mining sector is still the main sector of the state foreign exchange Indonesia has a social dimension of culture, economy and environment. The Act No. 4 of 2009 on Mineral and Coal (Mining Act) provides a new understanding of the concept of a modern mining law after all this time mining regime for more than 42 years in Indonesia are subject to the Act No. 11 of 1967 on Basic Provisions of Mining. The new Mining Law emphasizes the spirit of transparency, partispatif and environmentally sound. Mining Act and UUPPLH are expected can go hand in hand in terms of law enforcement aspects of preventive and repressive in every stages of mining activities have the greatest environmental aspects of exploration and exploitation because the object is on land where mining activities are always so for the environmental effects of pollution and environmental destruction. Mining Act (UU Minerba) and Protection and Environmental Management Act (UUPPLH) are expected to be a wheel mining activities that are not only economically profitable for the society of Indonesia but also environmentally sustainable and support Indonesia DevelopmentKeywords : Environmental Law, Mining Law, Law Enforcement